The political ambivalences of participatory planning initiatives. (August 2019) - Van Wymeersch, Elisabet; Oosterlynck, Stijn; Vanoutrive, Thomas
This article explores the relevance of combining multiple understandings of democratic politics to analyse the ambivalent and contentious dynamics of citizen participation in spatial planning. Building forth on the ongoing efforts in critical planning theory to overcome the deadlock between collaborative and agonistic oriented planning approaches, we argue for the refraining from 'over-ontologising' the question of democratic politics in planning processes, and start from the assumption that participatory planning processes as an empirical reality can accommodate radically different, even incompatible views on democracy. In addition, it is argued that while current planning scholars predominantly focus on the applicability of the collaborative and (ant)agonistic approach to democratic politics, a third approach – based on Jacques Rancière's notion of political subjectification grounded in equality – may be discerned. By mobilising an empirical study of a contentious participatory planning initiative in Ghent (Belgium), that is, the Living Street experiment, we illustrate that while different approaches to democratic politics do not necessarily align with each other, they are often simultaneously at work in concrete participatory planning processes and indeed explain their contentious nature.